Analysis of Landslide Prone Areas in Tampahan, Toba Samosir Regency, North Sumatra Province - Turnip, Winda Lestari; Jati, Stevanus Nalendra (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2020)
The topography of the Tampahan area which tends to be steep and dominated by tuff lithology can result in a landslide. The intensity of landslides and the resulting losses can be reduced by the analysis of landslide-prone areas in Tampahan. The administration of the area is located in Toba Samosir Regency, North Sumatra Province which is included in the Toba Caldera Region. Analysis of landslide-prone areas is carried out with five parameters namely slope, land use, morphological elevation, lithology, and rainfall. The data processed in this analysis comes from field data, DEMNas (National Digital Elevation Model), and other spatial data. Classification of each parameter and weighting based on literature is away in the analysis of landslide-prone areas of Tampahan. Then do each parameter overlay to get the value of landslide-prone and distinguished based on the calculation of the landslide class interval. The results are divided into five classes that are prone to landslides, namely classes not prone (1-1,8), rather prone (1,8-2,6), quite prone (2,6-3,4), prone (3,4-4,2), and very prone (4,2-5). Based on the analysis that has been done, some areas are very prone to landslides in the southeast while areas that are not prone to landslides are in the southwest of the study area. Therefore, landslide-prone studies are categorized as high landslides with almost 60% coverage of the study area.